Involvement of Muscarinic Receptors in Hypotensive and Diuretic Effects of Aqueous Soluble Fraction from Asphodelus tenuifolius Cav. (15th January 2021) - Younis, Waqas; Alamgeer,; Schini-Kerth, V. B.; Nocchi, Samara Requena; Silva, Denise Brentan; de Souza, Priscila; Bukhari, Ishfaq Ali; Vohra, Fahim; Afzal, Sibtain; Gasparotto Junior, Arquimedes
Abstract : Background . Asphodelus tenuifolius Cav. (Asphodelaceae) is widely used in Pakistan traditional medicine as a hypotensive and diuretic agent. Despite the cardioprotective effects described for A. tenuifolius, the mechanisms involved in its probable hypotensive and diuretic effects have never been evaluated. Firstly, different extracts from A. tenuifolius seeds were obtained, and their antioxidant profiles and chemical constituents by LC-DAD-were determined, including molecular networking by the GNPS platform. Then, to evaluate changes in blood pressure, different groups of anesthetized normotensive rats were intravenously treated with the crude extract (AT-Cr, 1–50 mg/kg), aqueous (AS-AT, 1–25 mg/kg), n-butanol (BS-AT, 1–50 mg/kg), and dichloromethane fraction (DS-AT, 1–80 mg/kg). The diuretic effects of AT-Cr, AS-AT, BS-AT, and DS-AT at 100, 200, and 300 mg/kg, p.o. doses, were also evaluated in comparison with hydrochlorothiazide (HCTZ, 10 mg/kg, p.o). The urinary volume, sodium, potassium, and pH were estimated in the sample collected for 6 h from saline-loaded rats. Using pharmacological antagonists or inhibitors, we determine the involvement of acetylcholine, prostaglandins, and nitric oxide in A. tenuifolius -induced hypotensive and diuresis action. In addition, the activities of angiotensin-converting enzyme, erythrocyte carbonic anhydrase, and renal Na+/K+/ATPase were evaluated in vitro . Acute treatment with crude extract and fractions of A. tenuifolius exhibited significant hypotensive and diuretic potential in normotensive rats. However, AS-AT produced the most potent and significant dose-dependent hypotension and diuretic effects in normotensive rats. Previous treatment with atropine significantly reduced the hypotensive and diuretic action of AS-AT, but pretreatment with indomethacin or L-NAME did not affect these effects. Moreover, the 7-day treatment with AS-AT did not reduce activities of serum angiotensin-converting enzyme, erythrocyte carbonic anhydrase, and renal Na+/K+/ATPase. AS-AT showed four major compound node clusters, which included sugars, alkaloids, nucleoside, amino acid, and glycosylated flavonoids. This research supports and extends the traditional use of A. tenuifolius as a hypotensive and diuretic agent. The results showed that AS-AT from A. tenuifolius could present compounds responsible for hypotensive and diuretic activities through the activation of muscarinic receptors.